1987
DOI: 10.1128/iai.55.5.1106-1115.1987
|View full text |Cite
|
Sign up to set email alerts
|

Identification and purification of a recombinant Treponema pallidum basic membrane protein antigen expressed in Escherichia coli

Abstract: A recombinant plasmid designated pLVS3 previously was described that harbored a 14-kilobase insert of Treponema pallidum genomic DNA. Escherichia coli maxicells programmed with this plasmid synthesized three treponemal protein antigens of molecular weights 39,000, 35,000, and 25,000 (39K, 35K, and 25K proteins, respectively). In this study, a detailed deletion analysis of pLVS3 demonstrated that the genetic information for all three protein antigens is contained within a 1.5-kilobase EcoRI-HpaI restriction fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 53 publications
3
21
0
Order By: Relevance
“…Whether the 20-kDa protein is expressed in T. pallidum is unknown. A similar result was observed with the recombinant 39-kDa basic membrane protein of T. pallidum (14). Complementation of an ompA mutation with tpn5O.…”
Section: Discussionsupporting
confidence: 80%
“…Whether the 20-kDa protein is expressed in T. pallidum is unknown. A similar result was observed with the recombinant 39-kDa basic membrane protein of T. pallidum (14). Complementation of an ompA mutation with tpn5O.…”
Section: Discussionsupporting
confidence: 80%
“…A characteristic feature of the 47-kDa antigen produced either by T. pallidum or by E. coli recombinant clones and analyzed by SDS-PAGE is the frequent presence of a 48-kDa component that reacts with specific polyclonal and monoclonal antibodies (4,11,20,22). It has been suggested that the 48and 47-kDa doublet seen in this and other studies (4, 11,20,22) is the result of inefficient (8) and/or incomplete processing of the 47-kDa antigen. Although it is considered unlikely, it was important to investigate this, particularly in light of the absence of demonstrable processing in E. coli.…”
Section: Discussionsupporting
confidence: 48%
“…Analyses of the genetics of flagellar expression in other bacteria have proved useful in understanding the genetic organization and control of complex operons (25). Furthermore, analysis of the upstream DNA may provide additional insights into our emerging understanding of the processing of treponemal antigens expressed in E. coli (12,21). In concert with attempts to achieve continuous in vitro cultivation of T. pallidum, the ultimate goal of these studies will be to use the derived genetic information along with mutational analyses to elucidate the relationships between motility and virulence, as has been accomplished with other bacterial pathogens (15).…”
Section: Discussionmentioning
confidence: 99%